KARAKTERISTIK PEMBELAJARAN ILMU PENGETAHUAN SOSIAL (IPS) DI SMP NEGERI 1 SELOGIRI - NURHAYATI , ELISABETH (2011)
Learning Social Studies (IPS) in SMP Negeri 1 Selogri indicate that there are still some students who are not yet capable of achieving individual competence required to follow the social studies lesson. Students are less able to apply concepts into everyday life. This means that the characteristics of students in SMP Negeri 1 Selogiri require a higher quality learning model, making it more able to apply science in everyday life. The purpose of this study was to describe the characteristics of RPP learning, characteristics of interaction between teachers and students, and the characteristics of the learning activities of the IPS. Sub focus in the research is lesson plan characteristics, teachers and students interaction characteristic, and learning prosses characteristic. This research is descriptive research with qualitative methods. Study presented conducted in SMP Negeri 1 Selogiri Wonogiri. Tehnik District data collection using in-depth interviews, observation and documentation. Technical analysis of the data in this study include data reduction, data and drawing conclusions. The validity of data is done by triangulation techniques or cross- checking data. The results showed that: (1) Characteristics of Learning Implementation Plan (RPP) social studies subjects in SMP Negeri 1 Selogiri already perform in accordance with the prevailing concept of curriculum (SBC). Teachers are given the freedom to change, modify, and adjust the syllabus to schools and local conditions, and with student characteristics. (2) Characteristics of the management of teacher-student interactions on teaching social studies at Junior High School 1 Selogiri been running well as adhere to the principle that the responsibility remains with the self-study students, and teachers are only responsible for creating situations that encourage initiative, motivation, and responsibility student responsibility for learning. Then to achieve competence, teachers lead students is easier because it uses a contextual approach to the link between the material taught with real situations and encourage students to make connections between knowledge Siwa held with an application in everyday life. (3) Characteristics of learning the implementation of IPS in SMP Negeri 1 Selogiri been implemented by following the principles of educational specialties, ie activities that focus on the activities of students active in building the meaning or understanding. Implementation of the learning starts from the initial activity (preparation), the core activities of learning (the formation of competence), and closing activities (evaluation and remedial).